Eksistensi Rumah Adat Desa Pengotan, Bangli - Ni Kadek Anggara Dwi Putri; A.A.N. Anom Kumbara; I Wayan Suwena (Department of Anthropology Udayana University, 2022)
Pengotan Village is Bali Aga’s villages which located in district of Bangli, Regency of Bangli, which has art in the form of sacred architectural art. The era of globalization that encourages people to renovate traditional houses more modern. This research studies how long this traditional house can be maintained the existence. This study was intended 1) To give the people a knowledge of the traditional house of the Pengotan Villages as one of the cultural heritage that has historical, artistic, traditional, and scientific values, 2) To find out the functions and factors that maintain the existence of the traditional house of Pengotan Village. This study uses qualitative research methods with the main way of collecting data is by observation and interviews. The theory used in this study is the structural functional theory of Robert K Merton. The results of the study reveal that the existence of traditional houses in Pengotan Village is still preserved even though a small part of the traditional houses have been renovated with newer innovations but still have the same shape and meaning.